Arthroscopic Remplissage Before Bankart Repair With All-Suture Anchor Mattress Fixation in the Beach-Chair Position - Alexander R. Markes, M.D.; Luke Sang, B.S.; Elliott Cole, M.D.; Brian T. Feeley, M.D. (Arthroscopy Techniques)
A common procedure for treatment of Hill-Sachs lesions in the setting of anterior shoulder instability is arthroscopic remplissage. Remplissage consists of using the posterior capsule and infraspinatus tendon to fill the Hill-Sachs lesion and convert it into an extra-articular defect. Previous versions of this technique have not specified the timing in which remplissage and Bankart repair occur and have been performed with the patient in the lateral decubitus position. In this Technical Note, we describe our technique where we perform the remplissage before Bankart repair using all-suture anchor mattress fixation with the patient in the beach-chair position. By performing the remplissage before Bankart repair, the shoulder is reduced to allow for easier execution of the remplissage and reduce difficulties that might prevent its completion if done after Bankart repair. Further, by completing remplissage before Bankart repair in the beach-chair position, the humeral head is moved posteriorly with the cuff to allow for better access for the following labral repair and allows for the standardization between arthroscopic and open shoulder instability management.